Steroid excretion and metabolism by gonadal tissue from a subject with testicular feminization syndrome. Issue 2 (February 1974) - Lockwood, E.; Ghosh, P. C.; Pennington, G. W.; Tipton, R.
Abstract : The initial clinical, pathological, and hormonal investigation of a patient with testicular feminization syndrome is described. Incubation of gonadal tissue with various radioactive substrates, together with the isolation and identification of the resulting metabolites, was demonstrated a high capacity to synthesize testosterone. Two biosynthetic pathways were demonstrated, originating from progesterone and pregnenolone. These are essentially similar to those of the normal adult testes. Low levels of activity were found in the phenolic fractions and no measurable production of oestrone, oestradiol, or oestriol was found.